Social Networks and Factor Markets: Panel Data Evidence from Ethiopia - Kibrom A. Abay; Goytom Abraha Kahsay; Guush Berhane (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
In the absence of well-established factor markets, the role of indigenous institutions and social networks can be substantial for mobilizing factors for agricultural production. We investigate the role of an indigenous social network in Ethiopia, the iddir, in facilitating factor market transactions among smallholder farmers. Using detailed longitudinal household survey data and employing a difference-in-differences approach, we find that iddir membership improves households' access to factor markets. Specifically, we find that joining an iddir network improves households' access to land, labor and credit transactions between 7 and 11 percentage points. Furthermore, our findings also indicate that iddir networks crowd-out borrowing from local moneylenders (locally referred as Arata Abedari), a relatively expensive credit source, virtually without affecting borrowing from formal credit sources. These results point out the roles non-market arrangements, such as social networks, can play in mitigating market inefficiencies in poor rural markets.
Keywords: D02; D13; D71; D83; D85; J46; O17; Q12; 330; Social networks; iddir networks; factor market imperfections; factor market transactions; crowding-out